2020
DOI: 10.2174/1570159x17666191021111809
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Overview of Chlorogenic Acid and its Metabolites in Chronic Pain and Inflammation

Abstract: Background: Natural phenolic compounds in medicinal herbs and dietary plants are antioxidants which play therapeutic or preventive roles in different pathological situations, such as oxidative stress and inflammation. One of the most studied phenolic compounds in the last decade is chlorogenic acid (CGA), which is a potent antioxidant found in certain foods and drinks. Objective: This review focuses on the anti-inflammatory and antinociceptive bioactivities of CGA, and the putative mechanisms of action are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 163 publications
2
46
0
Order By: Relevance
“…Moreover, CGA200 significantly reduced the creatinine and urea levels induced by As toxicity to normal levels and prevented inflammation, apoptosis, and oxidative stress in the kidney following exposure to As by increasing the expression of antioxidants, apoptotic inhibitors, and free radical scavengers. We attribute these results to the presence of the catechol group in CGA, which scavenges intracellular As‐induced and H 2 O 2 ‐induced ROS free radicals and then stimulates the protein expressions of all antioxidants (e.g., CAT and SOD) 11–13 . Moreover, we observed that CGA had a strong antiapoptotic effect, as demonstrated by a significant ability to upregulate the expression of the antiapoptotic protein Bcl‐2 and downregulate the expression of the proapoptotic caspase 3 and Bax.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Moreover, CGA200 significantly reduced the creatinine and urea levels induced by As toxicity to normal levels and prevented inflammation, apoptosis, and oxidative stress in the kidney following exposure to As by increasing the expression of antioxidants, apoptotic inhibitors, and free radical scavengers. We attribute these results to the presence of the catechol group in CGA, which scavenges intracellular As‐induced and H 2 O 2 ‐induced ROS free radicals and then stimulates the protein expressions of all antioxidants (e.g., CAT and SOD) 11–13 . Moreover, we observed that CGA had a strong antiapoptotic effect, as demonstrated by a significant ability to upregulate the expression of the antiapoptotic protein Bcl‐2 and downregulate the expression of the proapoptotic caspase 3 and Bax.…”
Section: Discussionmentioning
confidence: 64%
“…The findings of Lafay et al 11 . and Bagdas et al 13 . regarding phenolic compounds (such as CGA) having potential roles in regulating nutrient (e.g., protein and lipid) metabolism in liver tissues may explain the improvements in the bwt of animals following the combined exposure to CGA and arsenite.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Stress and corticosterone are known to cause dysbiosis of the gut microbiota [54,55], and a high level of glucocorticoid in the morning but not in the evening may be involved in this response. Chlorogenic acid derived from the A. lappa causes the increase of diversity [56]. If chlorogenic acid taken in the evening showed a stronger effect, as with catechin-rich tea [53], A. lappa root powder may provide a stronger effect on microbiota diversity with evening intake.…”
Section: Discussionmentioning
confidence: 99%
“…Three phenolic acids and one flavonoid in PFLE were identified and quantified by HPLC-DAD and the results are summarized in Table 1. antidiabetic, and anti-inflammation (Bagdas et al, 2019;Natarajan et al, 2017;Srinivasulu et al, 2018).…”
Section: Hplc-dad Analysesmentioning
confidence: 99%